Estimating under- and over-reporting of drinking in national surveys of alcohol consumption: Identification of consistent biases across four English-speaking countries - Stockwell, Tim (Addiction, 2016)
BACKGROUND AND AIMS: Questions about drinking “yesterday” have been used to correct under-reporting of typical alcohol consumption in surveys. We use this method to explore patterns of over- and under-reporting of drinking quantity and frequency by population sub-groups in four countries. DESIGN: Multivariate linear regression analyses comparing estimates of typical quantity and frequency of alcohol consumption with and without adjustments using the Yesterday method. SETTING AND PARTICIPANTS: Survey respondents in Australia (n=26,648), Canada (n=43,370), USA (n=7,969) and England (n=8,610). MEASUREMENTS: Estimates of typical drinking quantities and frequencies over the past year plus quantity of alcohol consumed the previous day. FINDINGS: Typical frequency was underestimated by less frequent drinkers in each country. For example, after adjustment for design effects and age, Australian males self reporting drinking “less than once a month” were estimated to have in fact drunk an average of 14.70 (±0.59) days in the past year compared with the standard assumption of 6 days (t=50.5, p<0.001). Drinking quantity “yesterday” was not significantly different overall from self-reported typical quantities over the past year in Canada, USA and England but slightly lower in Australia (e.g. 2.66 vs 3.04 drinks, t=20.4, p<0.01 for women). CONCLUSIONS: People who describe themselves as less frequent drinkers appear substantially to under-report their drinking frequency, but country and sub-group specific corrections can be estimated. Detailed questions using the Yesterday method can correct under-reporting of quantity of drinking.